PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KEBAHAGIAAN KARYAWAN (Studi Empiris pada Karyawan SMAN 1 KASIHAN BANTUL - Riza Widyantoro (MNJ 16 UMY 240, 2016)
This study aimed to analyze the Influence of Leadership, Work Environment, Job Satisfaction to Happiness by employees of SMA Negeri 1 in Kasihan Bantul, Yogyakarta. Subjects in this study were employees of SMA Negeri 1 Kasihan Bantul. In this study, a sample of 60 respondents were selected using random sampling method. The data used in this study is derived from the primary data. Collecting data using questionnaire techniques. The analysis tool used is multiple regression. Based on the analysis that has been done shows that the leadership style and job satisfaction positive and significant impact on the level of happiness of employees. Working Environment no significant effect on happiness levels of employees. Keywords: leadership, work environment, job satisfaction, employee happiness level